ANALYSIS OF THE POTENTIAL REVENUE OF BUSINESS SERVICE FEES AT THE TRANSPORTATION AND ENVIRONMENT OFFICE OF TOJO UNA-UNA DISTRICT - Handayani, Naniek; Kasim, Muhammad Yunus; Zainudin, Fatlina (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
This study aims to determine and analyze the growth rate and contribution of each type of business service levy, the effectiveness and efficiency of each type of business service levy and the real potential of each type of business service levy. This type of research is quantitative research. The data used is primary data from observations and interviews and secondary data obtained from the Transportation and Environment Agency, covering time series data from 2020 - 2023. Descriptive statistical analysis using the growth rate analysis formula, contribution, effectiveness and efficiency.The results showed mixed performance. The growth of terminal retribution, parking lot retribution and water crossing retribution is  "Unsuccessful",  while  port  service  retribution  is  "Very  Successful".  Overall  contribution  to  local revenue  is  "Very  Insufficient".  Effectiveness  varies  from  "Less  Effective"  to  "Very  Effective". Meanwhile,  efficiency  varies  from  "Inefficient"  to  "Very  Efficient".  Retribution  for  the  use  of environmental  laboratories,  retribution  for  special  parking  lots  and  retribution  for  port  services  are identified as having great potential to increase local revenue. In contrast, terminal retribution and water crossing retribution no longer have potential due to regulatory changes.